The sea lamprey germline genome provides insights into programmed genome rearrangement and vertebrate evolution - Smith, Jeramiah; Timoshevskaya, Nataliya; Ye, Chengxi; Holt, Carson; Keinath, Melissa C.; Parker, Hugo J.; Cook, Malcolm E.; Hess, Jon E.; Narum, Shawn R.; Lamanna, Francesco; Kaessmann, Henrik; Timoshevskiy, Vladimir A.; et al. (Nature genetics, 2018)
A new assembly of the sea lamprey germline genome identifies genomic regions that are systematically eliminated from somatic tissue during early development. Comparative analysis gives new insight into vertebrate evolution.